The Exonerating Effect of “Voluntary Desistance” of the Attempt: What Begins Badly, Ends Badly? - Reaño Peschiera, José Leandro (2005)
Voluntary desistance represents a complex issue in criminal dogmatics. In this context, the author argues that impunity for voluntary desistance, regulated in legal systems such as German, Spanish and Peruvian, lacks a solid foundation and instead generates dysfunctional consequences in any legal-criminal system that seeks to protect individual autonomy. Consequently, in a legal system where individual autonomy is a fundamental principle, the ability of an individual to avoid criminal liability simply by voluntarily desisting from a criminal act already initiated, without consideration of the risk created, is contrary to the logic of a criminal system that seeks to safeguard social security and order. It is therefore proposed that the rules be reformed in such a way that voluntary desistance does not automatically exempt from criminal liability. This would allow for a balance to be struck between criminal intent and the protection of the autonomy of others.